Performing 'us' and 'other': Intersectional analyses of right-wing populist media. (June 2022) - Norocel, Ov Cristian; Saresma, Tuija; Lähdesmäki, Tuuli; Ruotsalainen, Maria
Finland and Sweden share the ideal of a Nordic welfare state, with gender equality as a central tenet. In both countries, right-wing populist parties have gained prominence in mainstream politics. Despite similar political agendas at the moment, these parties have different political histories, and different modes of expressing their anti-immigration pleas. In this comparative study, we examine how the distinction between 'us' and the 'other' is performed intersectionally in terms of gender, social class, ethnicity and 'race', and sexuality. For this purpose, we examine empirical material collected from the party newspapers of the Finns Party and the Sweden Democrats, because their content most closely reflects the ideological tenets of these parties. The chosen timeline stretches from 2007 until 2014 and entails the qualitative close reading of 16 issues of each newspaper. We evidence the dynamic between the intersectional analysis that fleshes out the reproduction of categories of difference, and the comparative analysis with its interest in temporal change and the resulting convergence between the two parties' ideologies. We conclude that, although the Finns Party previously had a more pronounced anti-elitist rhetoric and resorted to class-based antagonism as a means to garner electoral support, it subsequently moved closer to the anti-immigration agenda around issues of protecting national identity and the welfare state that has characterised the political platform of the Sweden Democrats over the past decade. This temporal awareness allowed us to document the Sweden Democrats' ideological consistency over the examined timeframe, emphasising the party's quest to rebuild the (Swedish) 'people's home' and to exclude the racialised Muslim 'other'.